The Influence of School Principal Leadership and School Principal Competency on Teacher Performance through Work Culture - Anis Fuad; Uli Wildan Nuryanto; Yolla Sukma Handayani (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
This research is motivated by the important role of school principals in improving teacher performance, which in turn has an impact on the overall quality of education. Work culture is considered a mediating factor that can strengthen or weaken the relationship between leadership and principal competence and teacher performance. This research aims to analyze the influence of principal leadership and principal competence on teacher performance through work culture in State Elementary Schools in Pontang District, Serang Regency. The research method used is quantitative with a survey approach. Data was collected through 135 questionnaires distributed to teachers at State Elementary Schools in Pontang District. Data analysis was carried out using multiple regression statistical techniques and path analysis to test the relationship between variables. Based on the research results, it can be concluded that the principal's leadership (X1) and the principal's competence (X2) and work culture (Y) have a significant positive influence of 84.0% on teacher performance (Z) in State Elementary Schools in Pontang District, Regency. Attack. This means that teacher performance is influenced by 84.0% by the three exogenous variables, namely Principal Leadership, Principal Competency and Work Culture, while the remaining 16.0% is influenced by other variables outside the variables tested in this thesis model. These findings underline the need for special attention to developing work culture in the school environment as part of a strategy to improve teacher performance